Konfigurasi Mikrotik Untuk Internet RT/RW Jalan Selain Pematangraya - Nduru, Sastra Wandi; Purba, Gracia Agustina; Siringo Ringo, Arjun Alfeus Kresna Bahar; Zamelda, Olga; Silalahi, Saut Maruli (Program Studi Pendidikan Biologi, 2024)
Penelitian ini berjudul